Social media materialities and protest critical reflections (New York Routledge, 2019)
Far from being neutral, social media platforms - such as Facebook, Twitter, YouTube, and WeChat - possess their own material characteristics, which shape how people engage, protest, resist, and struggle. This innovative collection advances the notion of social media materialities to draw attention to the ways in which the wires and silicon, data streams and algorithms, user and programming interfaces, business models and terms of service steer contentious practices and, inversely, how technologies and economic models are handled and performed by users. The key question is how the tension between social media's techno-commercial infrastructures and activist agency plays out in protest. Addressing this, the volume goes beyond singular empirical examples and focuses on the characteristics of protest and social media materialities, offering further conceptualizations and guidance for this emerging field of research.-- Publisher's website.
gIntroduction Christina Neumayer, Mette Mortensen and Thomas Poell -- PART I. Spatiality. 1. I post, you rally, she tweets... and we all occupy: the challenges of hybrid spatiality in the Occupy Wall Street mobilizations Alice Mattoni -- 2. Rethinking networked solidarity Sky Croeser -- 3. Nomads of cyber-urban space: media hybridity as resistance Emiliano Trer?e -- PART II. Temporality. 4. (Social) media time, connective memory and activist television histories: the case of TV Stop (1987-2005) Tina Askanius -- 5. Facebook's communication protocols, algorithmic filters, and protest: a critical socio-technical perspective Lorenzo Coretti and Daniele Pica -- 6. Social media as activist archives Christina Neumayer and David M. Struthers -- Part III. Platformization. 7. Teorizing civic engagement and social media: the case of the "refugee crisis" and volunteer organizing in Sweden Julie Uldam and Anne Kaun -- 8. Materiality of clouds: beyond a platform-specific critique of contemporary activism Stefania Milan -- 9. "Please leave my news feed alone": exploring user protest against algorithmic personalization Martina Skrubbeltrang Mahnke -- 10. Evolving digital repertoires of contention in transitional societies: the case of China Jun Liu -- Afterword Lessons and puzzles in studying social media materialities and protest Alexandra Segerberg and W. Lance Bennett.
Prof. Belinda Espiritu (Recommending faculty) - Bookfair 2019
Includes bibliographical references and index.
Keywords: Social media -- Social aspects